2015
DOI: 10.1111/anae.13013
|View full text |Cite
|
Sign up to set email alerts
|

Effective local anaesthetic volumes for sciatic nerve blockade: a clinical evaluation of the ED99

Abstract: SummaryPrevious results in volunteers have indicated the effective dose in 99% of subjects (ED 99 ) of local anaesthetic volume to be 0.10 ml.mm À2 of cross-sectional nerve area for sciatic nerve blockade. The objective of this prospective, randomised, double-blind study was to investigate the ED 99 of local anaesthetic for ultrasound-guided sciatic nerve blockade in patients undergoing foot surgery, according to Dixon's up-and-down method and probit analysis. A starting volume of 0.20 ml local anaesthetic per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…With regard to therapeutic efficacy, anesthesiology groups have reported on the efficacy of US-guided sciatic nerve blocks at the distal thigh 33,34 and in the subgluteal region. 27 To our knowledge, there is only 1 previously published study reporting on the efficacy of therapeutic perineural sciatic nerve injection using a USguided transgluteal approach; this study of 10 patients reported a high rate of symptom reduction after a follow-up period of 2 months, although 2 of 10 patients had to undergo repeated injections after 2 weeks for persistent pain.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to therapeutic efficacy, anesthesiology groups have reported on the efficacy of US-guided sciatic nerve blocks at the distal thigh 33,34 and in the subgluteal region. 27 To our knowledge, there is only 1 previously published study reporting on the efficacy of therapeutic perineural sciatic nerve injection using a USguided transgluteal approach; this study of 10 patients reported a high rate of symptom reduction after a follow-up period of 2 months, although 2 of 10 patients had to undergo repeated injections after 2 weeks for persistent pain.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound-guided peripheral nerve blocks offer a number of advantages when compared with nerve stimulator techniques, both in terms of volumes of local anaesthetic administered and success rate [10][11][12]. The primary endpoint was postoperative local anaesthetic consumption in the first 48 h. A predictable consumption of local anaesthetic is a fundamental characteristic for continuous peripheral nerve blocks in the outpatient setting.…”
Section: Discussionmentioning
confidence: 99%
“…This confirms that tibial nerve catheter placement could be a reliable analgesic technique for ambulatory foot surgery. Ultrasound-guided peripheral nerve blocks offer a number of advantages when compared with nerve stimulator techniques, both in terms of volumes of local anaesthetic administered and success rate [10][11][12]. High-definition imaging has contributed to a better understanding of the structure of the sciatic nerve [13].…”
Section: Discussionmentioning
confidence: 99%
“…However, in general, the evaluation times of previous studies have been diverse (e.g., 30, 45, and 60 minutes) because the onset time of sciatic nerve block using ultrasound is 30 to 60 minutes. [911,17] …”
Section: Discussionmentioning
confidence: 99%
“…There have been a few studies on effective volumes for US-guided PSNB via the perineural route. [911] However, as far as we know, no previous study has sought to determine the minimum effective volume for surgical anesthesia via the subparaneural route. The purpose of the present study was to determine the MEV 50 and ED 90 for surgical anesthesia in US-guided PSNB via subparaneural injection.…”
Section: Introductionmentioning
confidence: 99%